Transcriptomic Landscape of Herbivore Oviposition in Arabidopsis: A Systematic Review - Ojeda-Martinez, Dairon; Diaz, Isabel; Santamaria, M. Estrella (Frontiers in Plant Science, 2022)
Herbivore oviposition produces in plants all sorts of responses, involving wide and complex genetic rearrangements. Many transcriptomic studies have been performed to understand this interaction, producing a bulk of transcriptomic data. However, the use of many transcriptomic techniques across the years, the lack of comparable transcriptomic context at the time of publication and the use of outdated databases, are limitations to understand this biological process. The current analysis intends to retrieve oviposition studies and process them with up-to-date techniques and updated databases. To reduce heterogeneities, the same processing techniques were applied, and Arabidopsis was selected to avoid divergencies on plant taxa stress response strategies. By doing so, we intended to understand the major mechanisms and regulatory processes linked to oviposition response. DEG identification and co-expression network-based analyses were the main tools to achieve this goal. Two microarray studies and three RNA-seq analyses passed the screening criteria. The collected data pertained to the lepidopteran Pieris brassicae and the mite Tetranychus urticae, and covered a timeline from 3h to 144h. Among the 18221 DEGs found, 15406 were exclusive of P. brassicae (72h) and 801 were exclusive for the rest of the experiments. Excluding P. brassicae (72h), shared genes on the rest of the experiments were twice the unique genes, indicating common response mechanisms were predominant. Enrichment analyses indicated that shared processes were circumscribed to earlier time points, and after 24h the divergences escalated. The response was characterized by patterns of time-dependent waves of unique processes. P. brassicae oviposition induced a rich response that shared functions across time points, while T. urticae eggs triggered less but more diverse time-dependent functions. The main processes altered were associated with hormonal cascades (e.g., SA and JA), defence (ROS and glucosinolates), cell wall rearrangements, abiotic stress responses and energy metabolism. Key gene drivers of the identified processes were also identified and presented. The current results enrich and clarify the information regarding the molecular behaviour of the plant in response to oviposition by herbivores. This information is valuable for multiple stress response engineering, among other applications.